Sustainable Mobility and Operational Challenges of Trans Mamminasata Bus in Makassar City - Malik, Ihyani; Nurdiansyah B, Aldy (Jurnal Pemerintahan dan Politik Lokal, 2025)
This study examines the operational effectiveness of the Trans Mamminasata Bus as part of the Makassar City government's efforts to encourage environmentally friendly mobility and reduce public dependence on private vehicles. Although this program was initiated as a solution to overcome congestion and air pollution, its implementation still faces various obstacles such as low public awareness, limited integration of routes and fleets, minimal supporting infrastructure, and weak policies on limiting private vehicles. This study uses a qualitative approach through case studies and observations at congestion points in Makassar City. The results of the analysis show that although the Trans Mamminasata Bus has the potential to be an effective mode of public transportation, synergy is needed between government policies, community participation, and strengthening of facilities and infrastructure so that this public transportation can truly function optimally in creating an inclusive, efficient, and sustainable urban mobility system